COMPARISON OF AGREEMENTS FROM 4 PAY TV PLATFORMS SUCH AS NETFLIX, IQIYI, DISNEY HOTSTAR, AND WE TV REGARDING CONSUMER PROTECTION - Lusiana Febri Lestari; Sri Budi Purwaningsih (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the role of Indonesian positive law in regulating the sale of premium accounts through third parties and to assess the extent of consumer legal protection in such digital transactions. Method: The research adopts a normative juridical approach with a statutory and conceptual framework, supported by literature analysis and examination of relevant laws and regulations concerning e-commerce and consumer rights. Results: The findings reveal that current Indonesian legal provisions inadequately address the legality and consumer protection aspects of third-party premium account sales, creating a regulatory gap in the digital marketplace. The analysis indicates the need for clearer legal definitions, stronger enforcement mechanisms, and updated consumer protection frameworks to mitigate potential fraud and misuse. Novelty: This study contributes to the growing discourse on digital commerce law by highlighting the emerging legal implications of intangible digital goods transactions and proposing a structured legal perspective to enhance consumer protection in Indonesia’s rapidly evolving e-commerce environment.